Examining the Influences on pineapple growers' profits in Basarang District's Batu Nindan Village - Yudea, Andika; Beatris, Diana; Pungan, Yudi; Tiawon, Harin (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2024)
This research was conducted to analyze the characteristics of farmers and the profile of pineapple farming in Batu Nindan Village, Basarang District, Kapuas Regency, and to analyze the factors that influence the income of pineapple farming carried out by farmers in Batu Nindan Village, Basarang District, Kapuas Regency. This research was conducted in Batu Nindan Village, Basarang District, Kapuas Regency. The research location was chosen purposively to obtain the research objective, namely, to determine the factors influencing income in pineapple farming. The sample population that became research respondents was 35 pineapple farmers. This number is based on the sample determination method, classified as non-probability sampling. The analysis method used is descriptive data analysis. The research findings show that pineapple farmers' income in Batu Nindan Village is influenced by the size of the business, capital, amount of production, and labor. All variables show significant influence both partially and simultaneously